PENGARUH TRANSAKSI ALAT PEMBAYARAN DENGAN MENGGUNAKAN KARTU (APMK) TERHADAP INFLASI DAN PERTUMBUHAN EKONOMI DI INDONESIA - B21112011, Sindi Aryani (Jurnal Pembangunan dan Pemerataan, 2017)
Means of payment using the card are inovation of system payment side that give many benefits for Indonesia, namely simple to transaction especially in big amount, decrease cost of making/ spreading cash money, push to consume the goods and services because of followed by the efficiency of the transaction cost This research aims to analyze influence of means of payment using the card transaction about inflation and growing of economuc in Indonesia. This research using secondary data that is retrieved by Bank Indonesia and Centra Bureau of Statistics. Method of analysis that is used in this research in Simple linear regretion. The result of this research from 2005 to 2014 shows that if the transaction using APMK still growth is high. It shows if the interest of society still high about APMK as means of payment. Result of regretion shows that APMK transaction consists of nominal debit card transaction and nominal credit card transaction that is accumulated become growth of APMK value transaction influence in positive and significance about growth of economic in Indonesia, meanwhile growing of transaction value in means of payment using the card about inflation in positive influence but insignificance. Keyword : APMK, Growth of economic, inflation